Introduction to microaggressions LGBTQ+ - Limited, Assemble You (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. In this track, we'll cover what a microaggression is, the sometimes subtle but always harmful nature of microaggressions. We'll examine the microaggressions specifically experienced by LGBTQ+ people in the workplace and provide practical guidance for fostering a more inclusive workplace through more considered use of language. Learning Objectives Learn what a microaggression is Learn about the sometimes subtle (but always harmful) nature of microaggressions Learn about microaggressions specifically experienced by LGBTQ+ people in the workplace Learn ways of fostering a more inclusive workplace through more considered use of language.